Sustainability Practices and Profitability of Islamic Commercial Banks in Indonesia - Nur Hafidhoh Nur Hafidhoh; Wasyith Wasyith; Nur Fatoni Nur Fatoni (AL-ARBAH: Journal of Islamic Finance and Banking, 2026)
Purpose - This study aims to examine the influence of green banking practices, banking zakat, and Corporate Social Responsibility (CSR) disclosures on the Return on Assets (ROA) of Islamic Commercial Banks (Bank Umum Syariah/BUS) in Indonesia during the 2021–2024 period. Method - A quantitative approach is employed using secondary data collected through documentation methods, encompassing sustainability reports, annual reports, and audited financial statements published by each sampled Islamic Commercial Bank. Panel data regression analysis was performed using EViews 12, with model selection guided by the Chow test, Hausman test, and Lagrange Multiplier test. Result - Green banking and Corporate Social Responsibility (CSR) do not exert a statistically significant influence on ROA. In contrast, banking zakat demonstrates a positive and significant effect on ROA. Jointly, the three independent variables do not significantly explain variation in ROA, as indicated by the relatively low coefficient of determination (R² = 17.82%). Implication - The findings offer practical insight for Islamic banking managers and regulators regarding the limited short-term financial impact of green banking and CSR initiatives, while underscoring the strategic value of zakat management as a profitability-enhancing instrument. Originality - This study contributes to the literature by simultaneously testing green banking, banking zakat, and CSR against Islamic Commercial Bank profitability over the most recent available period (2021–2024), revealing a differentiated impact structure in which only banking zakat yields a significant positive effect on ROA. Keywords: Green Banking, Banking Zakat, Corporate Social Responsibility, Return on Assets, Islamic Commercial Banks, Triple Bottom Line; ESG, Panel Data